Characteristic of safety recovery zone and roadside hazard cases in malaysia road: A review - Kunji, Ahmad Kamal; Kusbiantoro, Andri; Zulkiple, Adnan; Ramli, Harzah M. (Penerbit Universiti Malaysia Pahang, 2018)
The increasing number of highway crashes and the rising rate of fatality on run-off-road accidents has alarmed institutions to introduce design guidelines, evaluate their outcomes and improve the guidelines accordingly. This paper presents a case study on some of the existing roadside hazards in Malaysia, their impact to motorists, and reviews the current related provisions in the published design guidelines. Observations and in-depth study were made to the selected existing roadside hazards and assess their compliance to the available design guidelines and recommend improvement to some areas. The scope of the study covers on roadside trees, lighting and signboard poles, drainage structures, kerbs and safety barriers. The previously planted trees of less than 100 millimetres diameter within the clear zone of 9 and 6 meters to rural and urban roads respectively have grown in size to more than 500 mm diameters over 15 years, and today they have become hazards and causing deaths or serious injuries to passengers. The lighting and signboard poles installed near to the travel lane have resulted in high impact collisions to the extent of splitting vehicles and killing the motorists. The current roadside drainage structures are made of concrete and some with rubble lined walls are harmful and have been killing and injuring motorists when they are placed within the roadside safety recovery zone or corridor that are meant for skidding errant vehicle to make recovery traversing back to travel lane. The study showed some roadside barriers are not correctly applied and have become hazards instead of protecting the motorists. The outcomes of the case study suggest improvement to the design guidelines and roadside physical condition to minimise hazards to motorists.